Peningkatan Pendapatan Mayarakat Desa Melalui Diversifikasi Produk: Studi Kasus Pengolahan Biji Nangka Menjadi Keripik - Selvy Yuliani; Aura Putri Abelia; Astrina Utami; Tiwany Arraya; Puspita Devi (Institut Nalanda, 2025)
Jackfruit seed chips are a processed food innovation that uses jackfruit seeds as the main raw material which is often thrown away. This research aims to develop diversification in the use of jackfruit seeds to make chips as a healthy food and provide benefits to the community. The manufacturing process begins with cleaning the jackfruit seeds, boiling to remove the bitter taste, drying to reduce the water content, and slicing thinly before frying or baking until crispy. Several researchers say that jackfruit seeds have quite high nutritional content, such as fiber, protein and carbohydrates, as well as a delicious taste and crunchy texture. This product offers an environmentally friendly alternative to healthy snacks, because it uses ingredients that are usually wasted, and has the potential to be developed commercially.